Associations between upper trunk rotation kinematics, shoulder and elbow joint kinetics and pitching performance in Australian baseball pitchers - Mine, K.; Jones, M.; Saunders, S.; Onofrio, B.; Crowther, R. G.; Milanese, S. (Journal of Sports Sciences, 2025)
Early upper trunk rotation has been associated with higher arm kinetics in American baseball pitchers. However, it has not been investigated in Australian pitchers. The purposes of this study were: (1) to investigate the reliability of 3D optoelectronic measurements of pitching mechanics; and (2) to examine the relationships between segmental angular kinematics (pelvis and trunk), arm kinetics and pitching performance (ball velocity and spin rate) in Australian pitchers. 16 healthy male amateur pitchers (age 25.4 ± .7.8 yrs) were recruited to participate. Fastballs were assessed by Vicon 3D motion analysis (Oxford Metrics, UK) and Rapsodo device (Rapsodo Inc. USA). Kinematic and kinetic outcomes were found to have good to excellent trial-to-trial reliability. This study also found that higher peak shoulder proximal force was significantly associated with later onset timing of upper trunk rotation (t = 3.40, p < 0.01). There were significant positive associations between the difference in the timings of peak upper trunk and pelvic angular velocities and both ball velocity (t = 2.89, p < 0.05) and spin rate (t = 2.77, p < 0.05). Training to delay the timing of peak upper trunk rotation angular velocity relative to pelvic rotation might help improve ball velocity and spin rate.